(untitled) (World of finance, 2019)
Introduction. Nowadays, innovation is not the only economic phenomena, which affects the growth of productivity of factors of production, growth of volumes of production, structural changes, economic growth and national competitiveness, etc. Now innovations have become identified with development and improvement in all areas of the economy, including banking business. The purpose of the article is to disclose the concept of “banking innovations” and then to study the current state of electronic banking innovations in Ukraine, to identify the main threats, which influence the development of innovations in the domestic banking system, and determine the prospects for the development of banking innovations. Results. The article defines the notion of “banking innovations”. The current state of electronic banking innovations and the influence of the Internet development on the banking services are considered. The essence of Internet banking is also revealed and its distribution in Ukraine and in Europe is analyzed. In addition, the article presents the main threats affecting the development of innovations in the banking system of Ukraine, and specifies incident cases and their consequences in Ukraine and in the world. The prospects for the development of banking innovations are considered, the most promising banking innovations that could be launched in Ukraine were proposed. Conclusions. In general banking innovations in Ukraine are not independent development of truly innovative and unique products, services or technologies at the world level. It`s noticeable that there is development in the field of electronic banking services. The undisputed leader in the implementation of innovation at all levels of its own activities is the PJSC PrivatBank. There are highlight key areas for improving innovation in the banking system of Ukraine, such as: the formation of innovation policy, the development of distance servicing, and improvement customer service. In addition, with the development of technologies, new threats to innovation in the banking system are emerging. So there should be given a lot of attention in order to be in demand and banking institutions need to keep pace with global innovation and trends.